2022
DOI: 10.48550/arxiv.2202.03421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Adiabatic Compression on Dark Matter Halos and the Radial Acceleration Relation

Pengfei Li,
Stacy S. McGaugh,
Federico Lelli
et al.

Abstract: We use a semi-empirical model to investigate the radial acceleration relation (RAR) in a cold dark matter (CDM) framework. Specifically, we build 80 model galaxies covering the same parameter space as the observed galaxies in the SPARC database, assigning them to dark matter halos using abundance matching and halo mass-concentration relations. We consider several abundance matching relations, finding some to be a better match to the kinematic data than others. We compute the unavoidable gravitational interacti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…While the earliest models used present-day virial mass as the proxy (Conroy et al 2006;Moster et al 2010;Behroozi et al 2010), more recent work has shown that fits to galaxy clustering are improved by instead using a quantity that scales with haloes' concentration (Reddick et al 2013;Lehmann et al 2017); this reflects, through the correlation of concentration and halo formation time, the fact that galaxies formed in haloes at 𝑧 > 0. SHAM also provides reasonable fits to galaxies' dynamical scaling relations, although there are indications that the galaxy mass-halo mass relation it implies is too curved and that the neglect of additional correlations in the galaxy-halo connection generates excess scatter in circular velocity at fixed mass (Trujillo-Gomez et al 2011;Desmond & Wechsler 2015Desmond 2017a,b;Li et al 2022).…”
Section: Subhalo Abundance Matchingmentioning
confidence: 99%
“…While the earliest models used present-day virial mass as the proxy (Conroy et al 2006;Moster et al 2010;Behroozi et al 2010), more recent work has shown that fits to galaxy clustering are improved by instead using a quantity that scales with haloes' concentration (Reddick et al 2013;Lehmann et al 2017); this reflects, through the correlation of concentration and halo formation time, the fact that galaxies formed in haloes at 𝑧 > 0. SHAM also provides reasonable fits to galaxies' dynamical scaling relations, although there are indications that the galaxy mass-halo mass relation it implies is too curved and that the neglect of additional correlations in the galaxy-halo connection generates excess scatter in circular velocity at fixed mass (Trujillo-Gomez et al 2011;Desmond & Wechsler 2015Desmond 2017a,b;Li et al 2022).…”
Section: Subhalo Abundance Matchingmentioning
confidence: 99%